Preparation, First Structure Analysis, and Magnetism of the Long‐Known Nickel Benzoate Trihydrate – A Linear Ni···Ni···Ni Polymer and Its Parallels with the Active Site of Urease. Issue 6 (15th January 2016) - Vráblová, Anna; Falvello, Larry R.; Campo, Javier; Miklovič, Jozef; Boča, Roman; Černák, Juraj; Tomás, Milagros
Abstract: Nickel benzoate trihydrate (1 ) has been prepared in single‐crystalline form by the reaction of nickel carbonate with benzoic acid in boiling aqueous solution. Its crystal structure comprises positively charged [Ni(Bz)(H2 O)2 ] n n + chains, benzoate anions, and one independent water molecule of solvation. The hexacoordinate Ni II centers in the chains are triply bridged by one syn‐syn carboxylato and two aqua bridges, and adjacent chains are linked by O–H··· O hydrogen bonds [O··· O distances are in the range 2.647(3)–2.684(3) Å] through solvate water molecules and benzoate anions. Thermal analysis revealed that1 is stable up to 100 °C; further heating led to full dehydration accompanied by an additional decomposition reaction, as characterized by IR analysis of the intermediates. The geometrical features of the Ni centers have been compared with similar features at the active sites of urease. The effective magnetic moment per formula unit µ eff has a value of 3.17 µ B at room temperature and upon cooling reaches a maximum value of 12.39 µ B at T = 4.6 K, which indicates ferromagnetic coupling between the nearest Ni II atoms [3.0671(1) Å] within the chains; at lower temperatures this is counteracted by zero‐field splitting. Abstract : Nickel benzoate trihydrate (1 ) has been prepared in single‐crystalline form by the reaction of nickel carbonate with benzoic acid in boiling aqueous solution. Its crystal structure and magnetic properties have been determined and are discussed.